Utilization of Slow Sand Filter to Reduce Wastewater Pollution Levels from Restaurant Operations - Rizki, Sekar Dwi; Didik Kuswadi; Evline Aunike Pasaribu; Nila Akhmila Rizka; Tiorida Mantanari (Indonesian Journal of Environment and Sustainability Issues, 2025)
Restaurant wastewater is categorized as domestic wastewater. It contains high levels of fats, spices, detergents, and cleaning agents, all of which can pose substantial environmental hazards if inadequately treated. This study compared the effectiveness of slow sand filters with various thicknesses of filter material and measured physical and chemical parameters, employing a combination of natural filter media, including gravel, silica sand, zeolite, and coconut fiber. The study assessed several water quality parameters, including pH, ammonia concentration, temperature, turbidity, and dissolved oxygen (DO). The results indicate that the filtration system effectively reduced ammonia concentrations to levels that comply with the regulatory standards. Parameters pH values had minor changes, they remained below the thresholds required by applicable regulations. A substantial reduction in turbidity was observed, while the effluent temperature remained within acceptable environmental limits. However, a decrease in DO levels was noted post-filtration, due to microbial activity and temperature dynamics within the filtration media. Overall, the findings suggest that slow sand filtration systems utilizing natural and locally available materials offer a low-cost, and environmentally sustainable alternative for the treatment of restaurant wastewater.